IMPLEMENTASI KEBIJAKAN SUBSIDI PELAYANAN KESEHATAN DASAR TERHADAP KUALITAS PELAYANAN PUSKESMAS DI KOTA SINGKAWANG - Lutfhan Lazuardi, R. Hendri Apriyanto Tjahjono Kuntjoro (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Health sector is inseparable from thedecentralized system of local autonomy. Health sector is aresponsibility of the local government, even though it isfrequently included in the political policies of a leader. Thedirection of healthcare service development, particularly atthe level of Health Center, has been maintained in the MayorsDecree of Singkawang No. 82/2009 on the subsidiary ofhealthcare in Kota Singkawang.Objective: To find out the quality of healthcare at the HealthCenters in relation to the primary healthcare subsidy based onthe perception of society, control/supervision of Local HealthOffice, management, service time, service capacity/type, andattitude of the health center staffs.Method: A descriptive research with case study design wasconducted in three Health Centers: Singkawang Tengah, SingkawangTimur, and Singkawang Utara Health Centers. Subjectsof the research were 15 health staffs and 111 patients.The data were collected using questionnaire, observation, andinterviews.Results: The research found a score of 3.3 for the healthcarein Singkawang Tengah, Singkawang Timur, and SingkawangUtara Health Centers. It means that the Health Center providedrelatively high quality healthcare. From the Reliability dimension,a score of 2.92 was found for Point 2 quick examinationservice with reference to the standard procedure and a scoreof 2.97 for Point 5, the timeliness of healthcare. From the Responsivenessdimension, a score of 2.77 was found for Point 3â the patients did not wait long to get the healthcare service âand a score of 2.94 for Point 4 â the working hour of the HealthCenter. Qualitative analysis showed that the Local Health Officecontrolled/supervised the Health Centers by means of utilization/visit reports and management. It was found that servicetime was frequently ignored and that service type/capacity atthe Health Centers was constrained by the availability of reagentsand medication. The health staffs tended to ignore servicequality and time and there was an indication of deviation inthe utilization/visit reports sent by the Health Centers.Conclusion: The Local Health Office did not have adequatetools to control/supervise the Health Centers, as evident fromthe aspect of management, service time, service type/capacity,and health staff attitude. Procurement of healthcare supplieswas hampered by bidding process and the health staffs needcontinuous training and development.Keywords: Health Office, Health Centers, Public Perception,and Healthcare quality